Strategi Pendidik Mengembangkan Dimensi Kreatif Peserta Didik pada P5 Kelas IV SDN 1 Kemenuh: Penelitian - Surya Arika Saputra; Ni Nyoman Mariani; Kadek Yudista Witraguna (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to explore the strategies used by educators to foster students' creativity through the Project to Strengthen the Profile of Pancasila Students (P5). It also examines the challenges encountered during the implementation of these strategies and analyzes their implications for developing students’ creative abilities in Grade IV at SD Negeri 1 Kemenuh. Theories used are constructivism and behaviorism. The research subjects are Grade IV educators and students at SD Negeri 1 Kemenuh. Data were collected through non-participant observation, interviews, document study, and literature review, then analyzed using an interactive qualitative method: data reduction, presentation, and conclusion drawing. The findings show that project-based and problem-based learning strategies encourage creativity through active participation, technology use, and hands-on practice. Challenges include limited time, facilities, and diverse student characteristics, yet they can be addressed through guidance and collaboration. The applied strategies positively impacted students' confidence, creative ideas, and learning enthusiasm.